Pulp canal obliteration after replantation of avulsed immature teeth: a systematic review. Issue 6 (2nd July 2015) - Abd‐Elmeguid, Ashraf; ElSalhy, Mohamed; Yu, Donald C.
Abstract: Background: Avulsion of permanent teeth is one of the most serious dento‐alveolar traumatic injuries. Pulp canal obliteration (PCO) is one of the consequences after replantation of avulsed immature teeth. The aim of this systematic review was to determine when calcification following replantation of an avulsed immature tooth begins and to evaluate the prevalence of PCO in these cases. Materials and methods: Electronic database MEDLINE via Ovid, PubMed, Cochrane, and Web of science databases were searched. Hand searching was performed through reference lists of endodontic and trauma textbooks, endodontic and trauma‐related journals, and relevant articles from electronic searching. Pooled data from the selected articles were analyzed for prevalence of healing and PCO as well as mean first evidence of PCO. Results: Pulp healing after replantation of immature teeth occurred in 32.9%, while pulpal necrosis occurred in 67.1% of teeth. PCO was the most frequent outcome of pulpal healing as it occurred in 96% of healed pulps. First evidence of obliteration was observed from 3 to 14 months with mean time of 9.5 months (95% CI = 4.5–14.5 months). Conclusions: PCO is considered the mechanism by which the pulp heals after replantation of avulsed immature permanent teeth. PCO is very fast and can be recognized radiographically during the first year from the onset of the trauma.